1975
DOI: 10.1021/ac60356a009
|View full text |Cite
|
Sign up to set email alerts
|

Separation of organic sulfides from aromatic concentrates by ligand exchange chromatography

Abstract: Alkyl and aryl sulfides were separated from aromatic hydrocarbons by liquid chromatography on a copper-loaded carboxylic cation exchange resin. The sulfides were strongly absorbed from n-pentane solution while the hydrocarbons eluted relatively rapidly and in the order of the increasing number of aromatic rings in the compound. Sulfides were then recovered from the column by backwashing with a mixture of pentane and ethyl ether. All sulfides examined were recovered from the column without loss. The separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Cyclic sulfides, Cj-to C3-dihydrobenzothiophenes, present as major compounds in the P-3 fraction, eluted in the P-3 fraction. Although the retentions of alkylbenzothiophenes are identical with those of alkyldihydrobenzothiophenes in GC, the alkyldihydrobenzothiophenes were isolated and identified in this study, some of which have been previously identified in crude 13 1415 JZ, 19 Figure 9. FPD gas chromatograms of (A) P-2 and (B) P-3 fractions of an SRC-I process solvent.…”
Section: Methodsmentioning
confidence: 62%
“…Cyclic sulfides, Cj-to C3-dihydrobenzothiophenes, present as major compounds in the P-3 fraction, eluted in the P-3 fraction. Although the retentions of alkylbenzothiophenes are identical with those of alkyldihydrobenzothiophenes in GC, the alkyldihydrobenzothiophenes were isolated and identified in this study, some of which have been previously identified in crude 13 1415 JZ, 19 Figure 9. FPD gas chromatograms of (A) P-2 and (B) P-3 fractions of an SRC-I process solvent.…”
Section: Methodsmentioning
confidence: 62%
“…which are responsible for Rf differences observed in different experiments. The (2) ethyl 0.534 0.477 0.600 0.600 (3) n-propyl 0.557 0.503 0.600 0.600 (4) isopropyl 0.545 0.497 0.603 0.600 (5) n-butyl 0.537 0.503 0.600 0.600 (6) ferf-butyl 0.545 0.520 0.603 0.603 (7) sec-butyl 0.545 0.508 0.603 0.603 (8) isobutyl 0.537 0.497 0.600 0.600 (9) In order to determine the effect of electron donation by the sulfur atom on chromatographic behavior of individual alkyl phenyl sulfides the ñM(corr) for Hg2+-chloroform data were plotted against Taft * substituent constants (Figure 1). The negative slope of the straight line Ryi(cozt, , ^ ) = "1-400 * -0.320, (r = 0.994) provides an evidence of an increase in ligand strength of the sulfur atom with an increase in electron donation from alkyl groups in the series of four isomeric butyl phenyl sulfides.…”
Section: Discussionmentioning
confidence: 99%
“…In the design of an LEG system, the choice of the column packings is one of the most important factors to be considered. Vough and Dooley reported early partial separation of some alkyl and aryl sulfides using a Cu(II) impregnated cationexchange resin column (11), although their system was not efficient. The recent development of high-performance liquid chromatography (HPLC) has led to the production of many types of silica gel based chelating packing materials for LEG, of which nitrogen-containing chelates are most commonly used.…”
Section: Literature Citedmentioning
confidence: 99%